Ghosts - Telgemeier, Raina; Lamb, Braden (New York, NY : Graphix, an imprint of Scholastic, 2016)
Catrina and her family have moved to the coast of Northern California for the sake of her little sister, Maya, who has cystic fibrosis. Cat is even less happy about the move when she is told that her new town is inhabited by ghosts, but Maya sets her heart on meeting one.
Keywords: Sisters -- Comic books, strips, etc; Ghosts -- Comic books, strips, etc; Moving, Household -- Comic books, strips, etc; Families -- California, Northern; Comic books, strips, etc; California, Northern -- Comic books, strips, etc; Comics (Graphic works); Graphic novels